Shaping the future of Gaza: How Europe could contribute to sustainable stabilisation - Muriel Asseburg (Stiftung Wissenschaft und Politik (SWP), 2024)
In reaction to the mass killings, atrocities, and hostage-taking by Hamas, the Palestinian Islamic Jihad and other militant groups on 7 October 2023, Israel declared war, further tightened the closure of the Gaza Strip, and started a military operation. More than four months into the war, there has been limited progress towards fulfilling Israel's war aims. At the same time, Gaza's civilian infrastructure and residential buildings have been largely destroyed, its population has been internally displaced, more than 27,000 Palestinians have been killed, and the humanitarian situation has become ever more horrific. As Israel's representatives have announced elements of a post-war order, and as military operations are increasingly determining facts on the ground, international actors have also started to engage on the topic of the 'day after'. Yet, the interests, priorities, and capabilities of the main protagonists hardly align. Still, the European Union (EU) and its member states should seek to contribute towards ending the war and sustainable stabilisation. Such efforts will have to address governance, security, reconstruction, and a political framework.
Keywords: 320; Gaza; Hamas; Israel; Hezbollah; hostages; tunnel system; UN Relief and Works Agency for Palestine Refugees in the Near East; UNRWA; EU Coordinating Office for Palestinian Police Support; EUPOL COPPS; Genocide Convention